2002
DOI: 10.1211/002235702320402026
|View full text |Cite
|
Sign up to set email alerts
|

A novel insulin formulation can keep providing steady levels of insulin for much longer periods in-vivo

Abstract: We have recently succeeded in preparing insulin-loaded microcapsules that release the insulin in a strictly controlled manner with little initial rapid release in-vitro or in-vivo. We show here the superiority of the best formulation prepared with co-poly(D,L-lactic/glycolic) acids (PLGA) (mean MW 5800, L/G ratio 50:50) with a main diameter of 15 approximately 30 microm in-vivo. When 3.2 % insulin-loaded PLGA microcapsules were subcutaneously given as a single dose to streptozotocin-induced hyperglycaemic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A body weight gain in diabetic rats was observed as fast as normal rats after single injection of insulin-loaded microspheres in 28 days. 16 The above study also found very little body weight gain of diabetic rats by daily injection of insulin solution. large number of macrophages and a few polymorphonuclear (PMN) cells were observed infiltrating into the connective tissue.…”
Section: Physico-chemical Characterization Of Microspheresmentioning
confidence: 56%
“…A body weight gain in diabetic rats was observed as fast as normal rats after single injection of insulin-loaded microspheres in 28 days. 16 The above study also found very little body weight gain of diabetic rats by daily injection of insulin solution. large number of macrophages and a few polymorphonuclear (PMN) cells were observed infiltrating into the connective tissue.…”
Section: Physico-chemical Characterization Of Microspheresmentioning
confidence: 56%
“…Some of the approaches that have been tried in order to reduce the initial burst of insulin and to control the release duration and stabilization of insulin are PEGylation of insulin and addition of zinc salts, ethanol and/or glycerol, hydroxypropyl-$-cyclodextrins, sugars, salts, cationic polyelectrolyte, and nonionic and ionic surfactants to insulin. 2,[7][8][9][10][11][12][13][14] A combination approach of two or more delivery systems such as nanoparticle-microsphere or microsphere-hydrogel has also been tried to control and prolong the release behavior of various proteins. [15][16][17][18] However, development of microparticleor nanoparticle-based delivery systems involve complicated manufacturing procedure, low drug loading, and low protein stability due to the presence of organic solvents, heat, and agitation.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 For proteins to be used as drugs, delivery via polymer particles overcomes many of the associated unfavorable pharmacokinetics and side effects. 14 Multiple emulsion solvent evaporation methods are considered to be simple and versatile, so have been widely used for the preparation of protein-entrapped polymer particles. 15,16 However, major limitations for successful utilization of this modality of protein delivery include the instability of proteins during formulation, lyophilization, storage, and polymer degradation.…”
Section: Introductionmentioning
confidence: 99%